2012
DOI: 10.1155/2012/361730
|View full text |Cite
|
Sign up to set email alerts
|

In SituExpression of Regulatory Cytokines by Heart Inflammatory Cells in Chagas' Disease Patients with Heart Failure

Abstract: Chagas' disease is caused by the protozoan parasiteTrypanosoma cruzi. The immune system plays an important role in the reduction of parasite load, but may also contribute to the development of lesions observed during the chronic phase of the disease. We analyzed cytokines produced by inflammatory heart cells in 21 autopsy samples obtained from patients with Chagas' disease divided according to the presence or absence of heart failure (HF). Left ventricular sections were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 28 publications
5
75
1
3
Order By: Relevance
“…TNF-α has been pointed out as a key molecule in the generation of ectopic TLO which might facilitate the perpetuation of inflammation in the heart. Cells expressing TNF-α and IFN-γ have been identified in heart tissues from patients with chronic chagasic cardiomyopathy [9], [50]. Our findings showing T-bet expression in areas of high inflammation and proliferation further confirmed a type 1 T cell response in patients with severe heart disease.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…TNF-α has been pointed out as a key molecule in the generation of ectopic TLO which might facilitate the perpetuation of inflammation in the heart. Cells expressing TNF-α and IFN-γ have been identified in heart tissues from patients with chronic chagasic cardiomyopathy [9], [50]. Our findings showing T-bet expression in areas of high inflammation and proliferation further confirmed a type 1 T cell response in patients with severe heart disease.…”
Section: Discussionsupporting
confidence: 77%
“…Lymphocytes in these lesions express lymphocyte function antigen-a (LFA-1), CD44, very late antigen-4 (VLA-4) [7] and cytotoxic lymphocyte antigen 4 (CTLA-4) [8]. A Th1 cytokine pattern predominated in the cardiac inflammatory cell infiltrate of Chagas disease patients with heart failure [9].Whereas some authors have shown increased peripheral levels of IFN-γ in patients with severe heart disease [10][12], other studies have demonstrated an inverse association between disease severity and IFN-γ production [8], [13], [14].We have previously shown that most IFN-γ-secreting T cells in response to T. cruzi display a low grade of differentiation but high expression of the inhibitory receptor CTLA-4 in the circulation of subjects with chronic T. cruzi infection [8], [15], [16]. Conversely, the total T cell compartment in Chagas disease patients is enriched in highly differentiated T cells compared to uninfected controls [15][17].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of Chagas disease is multifaceted, and may involve an autoimmune component in addition to protracted damage to myocytes and cardiac neuronal and vascular networks caused by parasites persisting in host tissues (Bonney et al 2011; Cummings and Tarleton 2003; Davila et al 1989; Girones et al 2007; Leon et al 2004; Ribeiro dos Santos et al 1992; Rossi 1990; Teixeira et al 2011; Zhang and Tarleton 1999). Both cytotoxic CD8+ effector T lymphocytes and IFN-γ-producing CD4+ T cells (Th1 cells), are important for controlling T. cruzi parasitosis (Hoft et al 2000; Hunter et al 1997; Kumar and Tarleton 2001; Rodrigues et al 2000; Tzelepis et al 2007), yet these T cells may also contribute to the development of pathogenic inflammation during T. cruzi infection (Bonney et al 2011; Gomes et al 2003; Laucella et al 2004; Minoprio 2001; Ribeiro dos Santos et al 1992; Rizzo et al 1989; Rocha Rodrigues et al 2012; Soares et al 2001; Tarleton et al 1996; Tarleton et al 1994). IL-17, which is produced by Th17 cells and other cell types, has been associated with both pro- and anti-inflammatory functions in other disease models, and may play an anti-inflammatory role during T. cruzi infection by indirectly down-regulating the functions of pro-inflammatory Th1 cells, without interfering with parasite clearance (Guedes et al 2012; Soares et al 2012; Tosello Boari et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Durante a fase crônica da infecção, o miocárdio de pacientes com CCC apresenta um infiltrado inflamatório com predominância de células correspondentes a uma resposta do tipo Th1, sendo composto principalmente por células T CD8 + , CD4 + e macrófagos (Abel et al, 2001;Higuchi et al, 1993;Milei et al, 1992;Morato et al, 1998;Reis et al, 1993;Rocha Rodrigues et al, 2012). Além disso, ocorre a produção de grandes quantidades de IFN-e TNF , por outro lado IL-4, IL-6, IL-7, e IL-15 são encontradas em pequenas quantidades no miocárdio (Abel et al, 2001;Cunha-Neto et al, 2005;Fonseca et al, 2007;Higuchi et al, 1993;Reis et al, 1993Reis et al, ,1997Rocha Rodrigues et al, 2012 (Kierszenbaum, 1980;Krettli, Brener, 1976).…”
Section: A Resposta Imuneunclassified
“…Além disso, ocorre a produção de grandes quantidades de IFN-e TNF , por outro lado IL-4, IL-6, IL-7, e IL-15 são encontradas em pequenas quantidades no miocárdio (Abel et al, 2001;Cunha-Neto et al, 2005;Fonseca et al, 2007;Higuchi et al, 1993;Reis et al, 1993Reis et al, ,1997Rocha Rodrigues et al, 2012 (Kierszenbaum, 1980;Krettli, Brener, 1976). A resposta celular é importante para o controle inicial da infecção, no entanto, uma resposta efetiva mediada por anticorpos é crítica para o aumento da sobrevivência.…”
Section: A Resposta Imuneunclassified